Association Between Secondary Botulinum Toxin A Treatment Failure in Cosmetic Indication and Anti-Complexing Protein Antibody Production - Rungsima Wanitphakdeedecha; Watsachon Kantaviro; Panittra Suphatsathienkul; Ploypailin Tantrapornpong; Chadakan Yan; Chalermkwan Apinumtham; Yuttana Srinoulprasert (Adis, Springer Healthcare, 2020)
Abstract Introduction Botulinum toxin A (BoT/A) treatment failure (BTF) affects patients subjected to repeated BoT/A exposure for cosmetic indications. BoT/A's general formulation contains core BoT/A and complexing proteins. BTF may be caused by antibody-induced treatment failure. Antibodies against core BoT/A can occur; however, anti-complexing protein antibodies have never been demonstrated, and tools for anti-complexing protein antibody detection have not been developed. The aim of this study was to evaluate immune involvement in BoT/A-nonresponsive patients. Methods Patients suspected of nonresponsiveness to BoT/A for cosmetic indications were recruited. All volunteers were categorized as BoT/A-responsive or BoT/A-tolerant according to frontalis testing with onabotulinumtoxinA (onaA). Twenty-two BoT/A-tolerant volunteers were recruited separately for frontalis testing with incobotulinumtoxinA (incoA). Anti-BoT/A and anti-complexing protein antibodies were quantified by special ELISA using sera from blood sampled before and after frontalis testing. Results Significantly higher levels of IgG against complexing protein were detected in onaA-tolerant sera but not in onaA-responders, leading to proposals that anti-complexing protein antibodies could cause onaA unresponsiveness. Some onaA-tolerant patients according to frontalis test with incoA were responsive to incoA. Newly developed absorption ELISA confirmed that incoA-responsive sera predominantly contained IgG against complexing proteins, whereas incoA-tolerant sera contained significant levels of IgG against core BoT/A. The presence of anti-complexing protein antibodies higher than 90.75% in sera of onaA-tolerant patients could respond to incoA. The ELISA technique might be employed as a tool to predict incoA responsiveness. Our frontalis testing after incoA treatment showed that anti-incoA IgG levels were not increased by incoA. Conclusions BoT/A-exposed patients may develop antibodies against core botulinum toxin and complexing proteins. Our study is the first to demonstrate that anti-complexing protein antibodies cause BTF. High levels of antibodies against complexing proteins can cause onaA unresponsiveness, although some patients were still incoA-responsive. Our developed ELISA to detect anti-complexing protein antibodies can determine whether onaA-tolerant patients respond to incoA without incoA frontalis testing.